Contribution of iranian chemists in research activities, on the occasion of the international year of chemistry (2011)
On the occasion of the International Year of Chemistry (2011), scientometric anal- ysis of the publications of Iran, Turkey, Egypt, Israel and Malaysia in all fields and also in four chemistry sub-categories were extracted from Scopus and a number of quantitative and qualitative measures of the publications were discussed. Based on these findings, Iran is the leading state among the investigated countries in the field of chemistry concerning the number of publications and Israel is the leading state followed by Iran when the qualitative measures are considered.